Holocene temperature evolution in the Northern Hemisphere high latitudes – Model-data comparisons. (1st October 2017) - Zhang, Yurui; Renssen, Hans; Seppä, Heikki; Valdes, Paul J.
Abstract: Heterogeneous Holocene climate evolutions in the Northern Hemisphere high latitudes are primarily determined by orbital-scale insolation variations and melting ice sheets. Previous inter-model comparisons have revealed that multi-simulation consistencies vary spatially. We, therefore, compared multiple model results with proxy-based reconstructions in Fennoscandia, Greenland, north Canada, Alaska and Siberia. Our model-data comparisons reveal that data and models generally agree in Fennoscandia, Greenland and Canada, with the early-Holocene warming and subsequent gradual decrease to 0 ka BP (hereinafter referred as ka). In Fennoscandia, simulations and pollen data suggest a 2 °C warming by 8 ka, but this is less expressed in chironomid data. In Canada, a strong early-Holocene warming is suggested by both the simulations and pollen results. In Greenland, the magnitude of early-Holocene warming ranges from 6 °C in simulations to 8 °C in δ 18 O-based temperatures. Simulated and reconstructed temperatures are mismatched in Alaska. Pollen data suggest strong early-Holocene warming, while the simulations indicate constant Holocene cooling, and chironomid data show a stable trend. Meanwhile, a high frequency of Alaskan peatland initiation before 9 ka can reflect a either high temperature, high soil moisture or large seasonality. In high-latitude Siberia, although simulations and proxy data depict high Holocene temperatures, these signals are noisy owing to a large spread in the simulations and between pollen and chironomid results. On the whole, the Holocene climate evolutions in most regions (Fennoscandia, Greenland and Canada) are well established and understood, but important questions regarding the Holocene temperature trend and mechanisms remain for Alaska and Siberia. Highlights: Proxy-based reconstructions and models agree in Fennoscandia, Greenland and Canada. General temperature trends: early-Holocene warming and subsequent gradual decrease. Important questions regarding the Holocene temperature trend remain for Alaska. In high-latitude Siberia, temperature signals are noisy due to low number of records.